Evaluation of Irrigation Solutions and Activation Techniques in Endodontic Therapy - Thanaa Ghani Nema; Hamsa Zaki Al-Assadi; Zaidoon Hasan Mohammed (Dentistry 3000, 2025)
The study examined the current practices of irrigation and activation techniques used by dental professionals in Iraq, focusing on the selection and application of chemical irrigants and adjunct techniques during endodontic therapy. A cross-sectional survey was conducted among 108 participants, including general dental practitioners (GDPs) and endodontic specialists. The survey aimed to capture detailed information about the choice of irrigation solutions, the duration, depth, and pressure of irrigation, and the adjunctive techniques employed, such as ultrasonic and sonic activation. The findings reveal that while sodium hypochlorite remains the most used irrigant, advanced activation methods like passive ultrasonic irrigation (PUI) are underutilized despite their proven benefits. Additionally, most respondents adjust their irrigation protocols depending on canal anatomy, with an emphasis on tailored approaches to achieve optimal disinfection. The study highlights the need for better training and access to modern irrigation tools to improve treatment outcomes.